THE EFFECT OF THE MAKE A MATCH COOPERATIVE MODEL ON IMPROVING CIVICS LEARNING OUTCOMES AT AL-FURQON ELEMENTARY SCHOOL - Nita Oviana (CV Grasta Glory, 2026)
Low student interest and learning outcomes in Civics, particularly Pancasila Education, indicate the need for innovative and engaging instructional strategies in elementary schools. This study aims to examine the effect of the Make a Match cooperative learning model on improving students’ learning outcomes in Pancasila Education. The study was conducted at Al-Furqon Elementary School to address classroom-based learning challenges. The research employed Classroom Action Research (CAR) consisting of two cycles involving elementary school students. Data were collected through classroom observations, learning outcome tests, and documentation. The results revealed that the implementation of the Make a Match cooperative model significantly improved students’ learning activities and understanding of Pancasila concepts. Learning became more enjoyable and interactive, as students were actively involved in finding matching pairs of question and answer cards while collaborating with their peers. The improvement in learning outcomes was indicated by a consistent increase in students’ average scores across the two cycles. In conclusion, the Make a Match cooperative learning model is effective in enhancing Civics learning outcomes in elementary school settings. This study implies that cooperative and game-based learning models can be used as effective alternatives to conventional teaching methods in Civics education. Future research is recommended to apply this model in different schools, grade levels, or subjects to examine its broader effectiveness and sustainability.